PMO-231 Ileal and colonic mucosal dendritic cell cytokine profiles differ at rest and after in vitro bacteria and pro-biotic challenge in postoperative Crohn's disease patients. (28th May 2012) - Murugananthan, A U; Bernardo, D O; Mann, E R; Tee, C T; Hart, A L; Arebi, N; Knight, S C; Al-Hassi, H O
Abstract : Introduction: Postoperative Crohn's disease (CD) recurrence predominantly affects the ileal mucosa at the ileo-colonic anastomosis with the colonic side often spared. Altered immune responses to bacterial flora are thought to be a driving force in the pathogenesis of CD recurrence. Gut dendritic cells (DC) are key in the initiation of immune response, through cytokine production, when stimulated with bacterial antigens. We postulate that differences between ileal and colonic DC resting characteristics and functional responses may be responsible for the propensity of recurrence to occur at the ileal aspect of the anastomosis. We aimed to assess ongoing intracellular cytokine production in DC from ileal and colonic postoperative CD mucosa and assess their functional response to bacterial stimulation and modulation with probiotics. Methods: Paired ileal and colonic biopsies were taken from postoperative CD patients at colonoscopy (n=11). Lamina propria mononuclear cells were collected after collagenase digestion. DC intracellular cytokine responses (IL-2, IL-6, IL-17a, TGFβ and INFγ) were assessed in basal conditions and after culture with LPS and two probiotic bacterial strains Bifidobacterium Longum; Lactobacillus Casei ( B longum and L casei ) using multi-colour flow cytometry. Results: Unstimulated ileal DC showed higher levels of ongoing intracellular production of pro-inflammatory cytokines than unstimulated colonic DC: IL6 (34.21±12.80 vs 10.47±3.574 cells/υl [mean±SEM], p=0.037), IL17a (24.62±12.38 vs 14.94±9.865 cells/υl, p=0.05, n=5) and TGFβ (74.12±17.96 vs 32±16.27 cells/υl, p=0.031). Incubation with LPS resulted in higher DC intracellular cytokine levels of INFγ in ileal derived DC with a borderline p value (27.49±12.61 vs 0.39±0.391 cells/υl p=0.06) but not colonic derived DCs (19.55±10.12 vs 12.40±7.039, p=0.6). L casei incubation, however, led to a larger decrease in ongoing TGFβ (−42.35±16.02 vs 4.42±11.46 cells/υl p=0.023) and INFγ (−14.76 ±7.196 vs 20.33±10.16 cells/υl-, p=0.05) DC cytokine production in colonic tissue compared with ileal. Conclusion: Ileal mucosa DC demonstrate a cytokine profile implicating a Th17 response compared with colonic mucosa. Upon bacterial stimulation with LPS ileal mucosa demonstrate increased INFγ DC production compared with unstimulated DC. These results suggest a role of for a Th1/Th17 response in driving post-operative CD recurrence. The probiotics L casei and B longum failed to show significant effects in modulation of intracellular cytokine production in ileal DC. Competing interests: None declared.